A Factorial Evaluation of Commuters' Satisfaction on Urban Mobility – An Indian Perspective - Chakraborty, Suman; Raghavendra,; Sengupta, Arijit (Prabandhan: Indian Journal of Management, 2018)
Major Indian cities experience traffic choking from early morning, and commuters face extreme difficulty in reaching their destinations. Many surveys and empirical research results concluded with loads of suggestions for the government and transport agencies in India in terms of reducing traffic congestion and raising the commuters' satisfaction. It is observed that travelling during late night in major Indian cities is also equally precarious and problem-inviting. This paper explored the problems faced by commuters travelling during late night in Bengaluru. The paper brought out the main findings of a field survey (that was conducted during late night) on commuters travelling by cabs as well as by public and private transport. Convenience sampling was used to select 120 respondents, and the data were collected through a structured questionnaire. Responses were taken randomly from the commuters during the night from both commuters and drivers. The study observed 19 statistically significant variables out of 32 variables selected from previous studies and a pilot study that was conducted, which influenced the satisfaction of commuters travelling in the city of Bengaluru. These variables were further grouped under 10 factors. The study used multivariate analytical tools to obtain results regarding the perception of commuters on travelling satisfaction. Interestingly, the respondents were not found to be safety conscious in the city of Bengaluru and were found to be less aware about safety while travelling, especially at late night.